Advancements in laboratory techniques for early cancer detection and monitoring - Shaheen, Heba Mustafa; Harbi, Abdulrahman Jaber; Khormi, Abdullah Mohsen; Abuzaid, Reda Salah; Alshahrani, Abdullah Muneer; Geteni, Mansoor Musa; Arkoubi, Nossiba Hussain; Al Suyan, Abdulrahman Mohammed; Banaemah, Majidah Bakr; Alqahtani, Essa Hasan (International Journal Of Community Medicine And Public Health, 2023)
In years, there have been advancements in laboratory methods for detecting and monitoring cancer at its earliest stages. These breakthroughs have revolutionized the field of cancer care with a focus on treatment strategies. This review explores a range of laboratory-based approaches, including biopsies, advanced imaging technologies like PET, MRI, and CT scans, genomic profiling techniques such as next-generation sequencing novel biomarkers, innovative assay platforms, and the use of artificial intelligence-driven analytics. Liquid biopsies are particularly valuable as they provide real-time insights into tumor dynamics and responses to treatment by analyzing circulating tumor cells and cell-free DNA. Advanced imaging modalities offer enhanced sensitivity and resolution for the detection and monitoring of tumors. Genomic profiling techniques help unravel the complexities of tumors to guide therapies. Novel biomarkers show promise in types of cancer by aiding in screening prognosis determination and treatment monitoring. Innovative assay platforms allow for the analysis of biomarkers to improve diagnosis. The integration of intelligence (AI) and machine learning has been instrumental in interpreting clinical and molecular data alongside traditional laboratory techniques. However, despite progress made far challenges related to standardization, cost effectiveness, and ethical considerations persist. It is crucial to integrate these techniques into clinical practice to fully exploit their potential in enhancing cancer care.